Spitz/Reed nevi: a review of clinical-dermatoscopic and histological correlation - Ana F. Pedrosa (Mattioli1885, 2016)
Background: Spitz/Reed nevi are melanocytic lesions that may mimic melanoma at clinical, dermatoscopic and histopathological levels. Management strategies of these lesions remain controversial.